(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
This article addresses the relationship between business ethics and globalization processes. It concludes that we require a new concept of company, able to perform the social and economic functions that globalization demands. The distinction between ethics and morals serves to reflect on the limits of the various interpretations of corporate social responsibility (CSR). Companies often tackle the “triple bottom line” without really integrating it into their business management, with no dialogue with their stakeholders, and from a standpoint guided by purely strategic considerations. It is argued that CSR presumes an integrated economic-sociel and ethical-strategic management.